Implementasi Teori Belajar Konstruktivistik dalam Pembelajaran Seni Rupa di SDN Gadingkasri Kota Malang - Umah, Devi Nikmatul; Maharani, Nadiva Syahdu (FONDATIA, 2024)
The constructivist approach is a learning approach where students form their knowledge independently. The aim of this research is to find out the implementation of constructivist learning theory in fine arts learning and to find out the obstacles that might arise. The research method used is qualitative with data collection techniques through observation, interviews, literature approach and documentation. The informant in this research was the 5th grade fine arts teacher at SDN Gadingkasri, Malang City. The results of this research indicate that the application of constructivist learning theory has gone well even though there are several obstacles in its application. Through the application of constructivist learning theory in learning by providing a project for students, it is hoped that it will be able to create Indonesian students who have an independent, creative character and have a lot of knowledge.